Dialogically Constructing a Culturally Sustaining Multilingual Family Literacies Approach in Early Childhood Settings - Pauline Harris; Elspeth McInnes; Amy Farndale; Gunay Aghayeva; Lauren Depares; Philip Evans (Social Sciences)
This paper explores a family literacies approach that is being co-constructed in a critical participatory action research project. The project is situated in two culturally and linguistically diverse early childhood settings where the researchers are collaborating with educators and with children and families who have recently arrived in Australia and are learning English as an additional language. In a quest to support and sustain children’s language, literacy, and cultural practices in their home/community languages and in English, we have focused on co-creating multilingual books with the children and their families that are in their languages and about their worlds. This paper examines the affordances and complexities of dialogically co-creating these books for supporting culturally and linguistically sustaining practices in diverse early childhood settings.